Evaluation of the favorability of faults to slip: the case of the 2024 Noto Peninsula earthquake - Ayaka Tagami; Tomomi Okada; Martha K. Savage; Calum Chamberlain; Toru Matsuzawa; Ryotaro Fujimura; Kazuya Tateiwa; Keisuke Yoshida; Ryota Takagi; Syuutoku Kimura; Satoshi Hirahara; Taisuke Yamada; et al. (Earth, Planets and Space)
Abstract The 2024 Noto Peninsula earthquake (M 7.6) occurred at a depth of approximately 15 km in the eastern part of Noto Peninsula. The high dip angle faults (50–60°) in this area were formed by the extensional stress field during the formation of the Japan Sea. However, those faults are now active as reverse faults (tectonic inversion faults) in the present compressional stress field. It is important to evaluate the favorability of the faults to slip in the current stress field numerically to understand under what conditions this large earthquake occurred, and where future earthquakes are likely to occur. Therefore, we estimated the stress field around the source region before the 2024 Noto Peninsula earthquake and evaluated the favorability of slip of the faults using slip tendency (ST) analysis. In the area around the Noto Peninsula, most earthquakes have reverse focal mechanisms, although there are some strike-slip focal mechanisms. The stress field we estimated favors reverse faulting with an NW–SE compressional axis. In addition, the direction of the principal stress axis and the fault strike are oblique in the western area of the Noto Peninsula (non-coaxial), it is possible to cause strike-slip faulting. The optimum value for the horizontal stress direction is rotated 20° clockwise from the western area to eastern area. Our analysis of fault models related to the 2024 Noto Peninsula earthquake showed large ST values, implying the faults were favorable to slip in the stress field before the Noto Peninsula earthquake. In addition, faults in the Noto Peninsula area identified before the Noto Peninsula earthquake, but which have not yet ruptured, show large ST values. The distribution of large ST values was consistent with the large measured slip amount. Although it is necessary to consider other factors such as the slip history of each fault, the Noto Peninsula earthquake was/is considered to have occurred under conditions that are well-suited to multi-fault rupture. Graphical Abstract